1990
DOI: 10.1017/s0033291700013234
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and diencephalic lesions in Korsakoff's syndrome: a clinical and scan study

Abstract: SYNOPSISTwenty-five male alcoholic Korsakoff patients were compared with age and sex-matched non-Korsakoff chronic alcoholics and healthy volunteers on clinical and CT brain scan parameters. The scans were assessed by planimetry, visual grading procedures and computerized analysis. Reliable measures of third ventricular size were developed.The Korsakoff patients had wider third ventricles, larger lateral ventricles and wider interhemispheric fissures than the comparison groups; but sulcal and Sylvian fissure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 41 publications
3
32
0
1
Order By: Relevance
“…However, other authors have failed to find such a decline in medial temporal lobe volumes [24,31,37]. Linear increases with advancing age were found for the volume of the third ventricle (taken as an index for atrophy of the dorsomedial thalamus [19]). This is consistent with previous reports (e.g.…”
Section: Normal Brain Agingmentioning
confidence: 94%
See 2 more Smart Citations
“…However, other authors have failed to find such a decline in medial temporal lobe volumes [24,31,37]. Linear increases with advancing age were found for the volume of the third ventricle (taken as an index for atrophy of the dorsomedial thalamus [19]). This is consistent with previous reports (e.g.…”
Section: Normal Brain Agingmentioning
confidence: 94%
“…Based upon what is known from patient studies (e.g. [17,33,38,39]), it was expected that reductions in total brain volume would be related to a decline in performance on global cognitive tests measuring speed of mental processing, whereas atrophy of limbic structures (hippocampus, parahippocampal gyrus and mamillary bodies; and third ventricle as an index for the dorsomedial thalamus [19]) would be specifically associated with a deterioration on memory tests. We found a somewhat different pattern.…”
Section: Relation Between Brain Volumes and Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Discutiram a idéia de que existe no lobo frontal dos alcoolistas atrofia por eles considerada como típica e que progressivamente os doentes apresentariam lesões atróficas que iniciariam pela região frontal. Jacobson & Lishman (1990) …”
Section: Revisão Dos Instrumentos De Diagnóstico Médico-forense No Alunclassified
“…Neuroimaging studies have shown ventricular and sulcal enlargement in both Korsakoff and non-Korsakoff alcoholics (Aasly et al, 1993;Christie et al, 1988;Jernigan et al, 1991aJernigan et al, , 1991bLitton et al, 1993;Nicolas et al, 1997;Pfefferbaum et al, 1992;Rosse et al, 1997). Additionally, lesions or parenchymal volume loss have been noted in the diencephalon (Jernigan et al, 1991a;Paller et al, 1997), mamillary bodies (Bigler et al, 1989), cerebellum (Cala et al, 1978), orbital frontal regions (Jacobson & Lishman, 1990;Jernigan et al, 1991aJernigan et al, , 1991b, parietal and superior frontal cortex along with mesial temporal cortex (Jernigan et al, 1991b;Sullivan et al, 1996), and corpus callosum (Hommer et al, 1996). In addition, using MR imaging and neuropathological analysis some research suggests that white matter is more adversely affected than gray matter structures (Charness, 1993;Harper et al, 1985;Pfefferbaum et al, 1992;Sullivan et al, 1996).…”
Section: Neuroimaging and Brain Morphology In Substance Abuse And Tbimentioning
confidence: 99%